(±)-Equol does not interact with genistein on estrogen-dependent breast tumor growth. (February 2020) - Song, Huaxin; Hughes, Jennifer R.; Turner, Russell T.; Iwaniec, Urszula T.; Doerge, Daniel R.; Helferich, William G.
Abstract: Equol (EQ) is a prominent microbial metabolite of the soy isoflavone, daidzein, with estrogen-like properties. The major soy isoflavone, genistein (GEN), stimulated growth of estrogen-dependent breast cancer (EDBC) cells in vitro and tumor growth in vivo but EQ did not. To understand possible interactions of EQ and GEN on EDBC, EQ was used with GEN in combination in vitro and in vivo . Effects of EQ, GEN and EQ + GEN were evaluated using MCF-7 and T47D EDBC. Ovariectomized athymic mice were used as a model for in vivo tumor growth. Dietary EQ had no effect on MCF-7 tumor growth and the absence of effect was confirmed using a T47D EDBC in vivo model. EQ alone or in combination with GEN increased EDBC cell proliferation in vitro . EQ alone neither stimulated EDBC tumor growth in vivo at various doses nor suppressed tumor growth induced by dietary GEN. In summary, EQ has similar estrogenic effect as GEN in vitro but does not interact with GEN on EDBC tumor growth. Based on the evidence presented here, dietary EQ is unlikely to have estrogenic effects in vivo . Highlights: EQ is estrogenic in vitro on estrogen-dependent breast cancer cells. GEN stimulates growth of MCF-7 or T47D BC tumor cells in mice. EQ does not stimulate estrogen-dependent breast cancer growth in vivo. EQ does not alter the effect of GEN in vivo.